COMMUNICATION STRATEGIES USED BY A TEACHER IN TEACHING ENGLISH AT SMP SWASTA KATOLIK ASSISI MEDAN - Darman Pangaribuan; Erika Sinambela; Balazs Huszka (Jurnal Scientia, 2022)
This thesis aimed to find communication strategies used by teachers during classroom interaction. This research was conducted in SMP Swasta Katolik Assisi Medan. The subject of this research was the English Teacher. The researcher used a qualitative approach, more specifically classroom discourse analysis, in analyzing this study since the source of the data was communication strategies that are used by an English teacher in communicating with her students during an English teaching-learning activity. The data was taken by recording 90 minutes of English Lessons. The researcher used Celce-Murcia as a framework for this data analysis because of its specification and newness. The result showed that the five strategies used were repetition. From those strategies, code-switching was the strategy that was most frequently used by the teacher during the process of teaching and learning. The teacher`s reasons for applying those communication strategies were to overcome the communication barriers that occur between the teacher and the students and to help the students understand and memorize the material more accessible. The result of the interview also showed that the students had a good perception of the implementation of communication strategies used by the teacher in the classroom.